Strategies of traversing obstacles and the simulation for a forestry chassis. (2nd May 2018) - Zhu, Yue; Kan, Jiangming; Li, Wenbin; Kang, Feng
As to the complicated terrain in forest, forestry chassis with an articulated body with three degrees of freedom and installed luffing wheel-legs (FC-3DOF&LW) is a novel chassis that can surmount obstacles. In addition, the rear frame of FC-3DOF&LW is regarded as the platform to carry equipment. Small inclination angle for rear frame contributes to stability and ride comfort. This article describes the strategy of traversing obstacles and simulation for FC-3DOF&LW that drives in forest terrain. First, key structures of FC-3DOF&LW are briefly introduced, which include articulated structure with three degrees of freedom and luffing wheel-leg. Based on the sketch of luffing wheel-leg, the movement range of luffing wheel-leg is obtained by hydraulic cylinder operation. Second, the strategy of crossing obstacles that are simplified three models of terrain is presented, and the simulation for surmounting obstacles is constructed in multibody dynamics software. The simulation results demonstrate that the inclination angle of rear frame is 18° when slope is 30°. A maximum 12° decrease of inclination angle for rear frame can be acquired when luffing wheel-legs are applied. For traversing obstacles with both sides, the maximum inclination angle of rear frame is about 1.2° and is only 3° for traversing obstacles with single side.